Development Of Qr Code-Based Ushiro Mawashi Geri Kick Exercise Variations For Junior High School Karate Athletes - Septi Suswanti; Onyas Widianingsih; Nikita; Julia; Raysa Miranda; Alya Andini; Abdillah Ramadhan; Andreyahbudiman (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to improve the results of the ushiro mawashi geri kick training ability based on qr codes in karate athletes at Mtss Alwashliyah Stabat and SMP Negeri 1 Sawit Seberang through the use of pocket books accompanied by qr codes. The research location was carried out at Mtss Alwashliyah Stabat and SMP Negeri 1 Sawit Seberang. This study uses a research and development method (Research and Development) with the Sugiyono development procedure. The population in this study was 30 athletes. The small group trial sample consisted of 10 Mtss Alwashliyah Stabat athletes and the large group trial sample consisted of 20 SMP Negeri 1 Sawit Seberang athletes. The data collection technique in this development research is using a questionnaire given to experts and athletes, the data analysis technique used in this development research is quantitative descriptive statistics. The Development of Ushiro Mawashi Geri Kick Training Variations Based on QR Codes in Junior High School Karate Athletes has first been validated by experts, namely material experts, language experts, and trainer experts. The results of the validation of the product design by experts were 71%, based on the assessment, the percentage was in the range of 71% -85% and was categorized as